Changes in Tannic Composition of Reproduction Cork Quercus suber throughout Industrial Processing - Cadahía, Estrella; Conde, Elvira; Fernández de Simón, Brígida; García-Vallejo, María Concepción (Journal of Agricultural and Food Chemistry, 1998)
Tannic composition was studied in reproduction cork samples from three different trees of Spanish Quercus suber and at different industrial processing stages. The ellagitannins, roburins A and E, grandinin, vescalagin, and castalagin, were identified and quantified by HPLC. Global evaluations of tannins were also carried out, using classical chemical methods. The group of hydrolyzable tannins was the most abundant in the tannic extract in all samples; among them, castalagin was the main component, followed by vescalagin, grandinin, roburin E, and, to a much lesser extent, roburin A. The changes in tannic composition throughout the industrial processing are mainly related to the boiling process and are more pronounced in total phenol and proanthocyanidin contents than in individual ellagitannins content. Vescalagin and roburins A and E were selected as those variables that provided the greatest discrimination among stages. Important differences in the ellagitannin contents were observed among the trees studied, all of the ellagitannins being discriminant variables in this case. Keywords: Quercus suber; cork; tannins; ellagitannins; proanthocyanidins; polyphenols; high-performance liquid chromatography
doi: 10.1021/jf9709360doi: 10.1021/jf9709360The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; ellagitannins; high performance liquid chromatography; polyphenols; proanthocyanidins; Quercus suber; Tannins

Changes in Tannic Composition of Reproduction Cork Quercus suber throughout Industrial Processing (Journal of Agricultural and Food Chemistry, 1998)
Tannic composition was studied in reproduction cork samples from three different trees of Spanish Quercus suber and at different industrial processing stages. The ellagitannins, roburins A and E, grandinin, vescalagin, and castalagin, were identified and quantified by HPLC. Global evaluations of tannins were also carried out, using classical chemical methods. The group of hydrolyzable tannins was the most abundant in the tannic extract in all samples; among them, castalagin was the main component, followed by vescalagin, grandinin, roburin E, and, to a much lesser extent, roburin A. The changes in tannic composition throughout the industrial processing are mainly related to the boiling process and are more pronounced in total phenol and proanthocyanidin contents than in individual ellagitannins content. Vescalagin and roburins A and E were selected as those variables that provided the greatest discrimination among stages. Important differences in the ellagitannin contents were observed among the trees studied, all of the ellagitannins being discriminant variables in this case. Keywords: Quercus suber; cork; tannins; ellagitannins; proanthocyanidins; polyphenols; high-performance liquid chromatography
doi: 10.1021/jf9709360

Chemical Characterization of Reproduction Cork from Spanish Quercus Suber - Conde, Elvira; Cadahía, Estrella; Garcia-Vallejo, Maria Conceptión; Gonźalez-Adrados, José Ramón (Journal of Wood Chemistry and Technology, 1998)
Abstract The chemical composition of Quercus suber reproduction cork was studied in planks from three different trees at different stages of their industrial processing and in samples collected in seven locations in the three main Spanish production areas. Extracts in chloroform, methanol and water, ne[ugrave]tral and acid fractions of waxes, suberin, lignin, holocellulose and pentosans, and polyphenols (low molecular weight polyphenols and tannins), were quantified. Suberin was the main component in all the samples, followed by lignin and holocellulose in lower concentrations. The most affected variables throughout the industrial processing were: lignin, chloroform and water extracts and the acid fraction of waxes. These variables did not allow one to distinguish the studied trees, which are differentiated by the percentages of methanol extracts, the tannic fraction of polyphenols, the free of suberin residue and the holocellulose content. Four variables were selected as those which provided the greatest discrimination among provenances: methanol extract, low molecular weight polyphenols, desuberinized residue and acid fraction of waxes. However, the studied populations can not be clearly distinguished by their chemical composition and no relationship was found between geographical proximity of their provenances and chemical resemblance.
doi: 10.1080/02773819809349592doi: 10.1080/02773819809349592The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: chemical composition; Cork; suberin; waxes (voyant)

Chemical Characterization of Reproduction Cork from Spanish Quercus Suber (Journal of Wood Chemistry and Technology, 1998)
Abstract The chemical composition of Quercus suber reproduction cork was studied in planks from three different trees at different stages of their industrial processing and in samples collected in seven locations in the three main Spanish production areas. Extracts in chloroform, methanol and water, ne[ugrave]tral and acid fractions of waxes, suberin, lignin, holocellulose and pentosans, and polyphenols (low molecular weight polyphenols and tannins), were quantified. Suberin was the main component in all the samples, followed by lignin and holocellulose in lower concentrations. The most affected variables throughout the industrial processing were: lignin, chloroform and water extracts and the acid fraction of waxes. These variables did not allow one to distinguish the studied trees, which are differentiated by the percentages of methanol extracts, the tannic fraction of polyphenols, the free of suberin residue and the holocellulose content. Four variables were selected as those which provided the greatest discrimination among provenances: methanol extract, low molecular weight polyphenols, desuberinized residue and acid fraction of waxes. However, the studied populations can not be clearly distinguished by their chemical composition and no relationship was found between geographical proximity of their provenances and chemical resemblance.
doi: 10.1080/02773819809349592

Polyphenolic Composition of Quercus suber Cork from Different Spanish Provenances (Journal of Agricultural and Food Chemistry, 1998)
Polyphenolic composition was studied by HPLC and classical chemical methods in reproduction cork of Quercus suber from different Spanish provenances. The low molecular weight polyphenols (gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferyl, and sinapic aldehydes; and aesculetin and scopoletin) and the ellagitannins (roburins A and E, grandinin, vescalagin, and castalagin) were identified and quantified. Ellagic acid was the main component in the ether soluble fraction, and the group of hydrolyzable tannins, and among them castalagin, was the most abundant in the tannic extract in all the samples. Although there was an important variability among provenances, no significant differences were found in the total tannin content and in the individual content of each ellagitannin. However, gallic and caffeic acids and protocatechuic aldehyde provided the greatest discrimination among provenances. Keywords: Quercus suber; cork; polyphenols; tannins; phenolic acids and aldehydes; coumarins; ellagitannins; high-performance liquid chromatography
doi: 10.1021/jf970863k

Polyphenolic Composition of Quercus suber Cork from Different Spanish Provenances - Conde, Elvira; Cadahía, Estrella; García-Vallejo, María Concepción; Fernández de Simón, Brígida (Journal of Agricultural and Food Chemistry, 1998)
Polyphenolic composition was studied by HPLC and classical chemical methods in reproduction cork of Quercus suber from different Spanish provenances. The low molecular weight polyphenols (gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferyl, and sinapic aldehydes; and aesculetin and scopoletin) and the ellagitannins (roburins A and E, grandinin, vescalagin, and castalagin) were identified and quantified. Ellagic acid was the main component in the ether soluble fraction, and the group of hydrolyzable tannins, and among them castalagin, was the most abundant in the tannic extract in all the samples. Although there was an important variability among provenances, no significant differences were found in the total tannin content and in the individual content of each ellagitannin. However, gallic and caffeic acids and protocatechuic aldehyde provided the greatest discrimination among provenances. Keywords: Quercus suber; cork; polyphenols; tannins; phenolic acids and aldehydes; coumarins; ellagitannins; high-performance liquid chromatography
doi: 10.1021/jf970863kdoi: 10.1021/jf970863kThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; coumarins; ellagitannins; high-performance liquid chromatography; phenolic acids and aldehydes; polyphenols; Quercus suber; Tannins

Low Molecular Weight Polyphenols in Cork of Quercus suber - Conde, Elvira; Cadahía, Estrella; García-Vallejo, María Concepción; Fernández de Simón, Brígida; González Adrados, José Ramón (Journal of Agricultural and Food Chemistry, 1997)
Low molecular weight polyphenols were studied by HPLC in samples of cork from different trees of Spanish Quercus suber and at different industrial processing stages. Gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferylic, and sinapic aldehydes, and aesculetin and scopoletin were identified and quantified. Ellagic acid was the main component in all of the samples, followed by the rest of the phenolic acids, which had very much lower concentrations. Four components, caffeic, ferulic, and protocatechuic acids and vanillin, were selected as those that provided the greatest differences among the trees studied. In relation to the four industrial processing stages considered, marked differences were observed between the first two stages, stripping and first rest, and the stages after boiling. In this case, the discriminant variables were coniferaldehyde, sinapaldehyde, and ellagic acid. Keywords: Quercus suber; cork; polyphenols; phenolic acids and aldehydes; coumarins; high-performance liquid chromatography
doi: 10.1021/jf960486wdoi: 10.1021/jf960486wThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; coumarins; high- performance liquid chromatography; phenolic acids and aldehydes; polyphenols; Quercus suber

Low Molecular Weight Polyphenols in Cork of Quercus suber (Journal of Agricultural and Food Chemistry, 1997)
Low molecular weight polyphenols were studied by HPLC in samples of cork from different trees of Spanish Quercus suber and at different industrial processing stages. Gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferylic, and sinapic aldehydes, and aesculetin and scopoletin were identified and quantified. Ellagic acid was the main component in all of the samples, followed by the rest of the phenolic acids, which had very much lower concentrations. Four components, caffeic, ferulic, and protocatechuic acids and vanillin, were selected as those that provided the greatest differences among the trees studied. In relation to the four industrial processing stages considered, marked differences were observed between the first two stages, stripping and first rest, and the stages after boiling. In this case, the discriminant variables were coniferaldehyde, sinapaldehyde, and ellagic acid. Keywords: Quercus suber; cork; polyphenols; phenolic acids and aldehydes; coumarins; high-performance liquid chromatography
doi: 10.1021/jf960486w